PENGARUH PEMBERIAN MINYAK ZAITUN TERHADAP PENYEMBUHAN ULKUS DIABETES MELITUS PADA PASIEN DIABETES MELITUS TIPE II - Hariati, Hariati; Ginting, Sulastri (Jurnal Kajian Kesehatan Masyarakat, 2019)
Diabetes Mellitus is the most common degenerative disease found. This disease is characterized by increased blood sugar levels and high levels of sugar in the urine due to impaired insulin secretion. Diabetes comes from the Greek word (diabainen) which means "pouring or showering" while the word millitus comes from the Latin word (millitus) which means "honey", this word describes the high sugar content in the urine of sufferers. Olive oil contains one chemical, oleocanthal that can prevent inflammation, similar to pain relievers such as ibuprofen and other anti-inflammatory drugs used as an external medicine to help heal tearing wounds, abrasions and other disorders that are at risk of inflammation, redness, swelling and pain.The research design used a one group pretest posttest design. The variables in this study were olive oil as the independent variable and the dependent variable on the healing of diabetic ulcers. The population in this study were all patients with Diabetes Mellitus type II who had Diabetic Ulcers. Sampling using purposive sampling technique of 14 respondents. The intervention will be carried out by giving olive oil. The data were collected using the observation sheet and the Wilcoxon test. The results showed that there was a cure for diabetic ulcers in people with Diabetes Mellitus type II. The result of the Shaphiro-Wilk data normality test before giving olive oil was 0,000 and after being given olive oil was 0.034. Paired sample test results show that the data p: 0.000 <Î±: 0.05, so Ho is rejected and Ha is accepted. This means that there is an effect of olive oil on the healing of diabetic ulcers in people with Diabetes Mellitus type II.